2006
DOI: 10.1152/ajpheart.00384.2006
|View full text |Cite
|
Sign up to set email alerts
|

Allicin in garlic protects against coronary endothelial dysfunction and right heart hypertrophy in pulmonary hypertensive rats

Abstract: We recently reported that coronary endothelial cell (CEC) dysfunction may contribute to the development of right ventricular (RV) hypertrophy (RVH) in monocrotaline (MCT)-induced pulmonary hypertensive rats. This present study investigated whether preservation of CEC function with garlic and its active metabolite allicin could abrogate RVH. Rats were fed with 1% raw garlic (RG)-supplemented diet 1 day or 3 wk before and 1 day after MCT injection, and changes in RV pressure (RVP), RVH, and CEC function were ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 25 publications
3
35
0
2
Order By: Relevance
“…Further testing of vasoactivity to garlic extracts showed that only RG, but not BG or AG, elicited a potent, dose-dependent dilation on the isolated coronaries. These findings show that positive effect of RG is probably mediated via its active metabolite allicin action on coronary endothelial function and vasoreactivity [121].…”
Section: Garlic and Endothelial Function Of Arteriesmentioning
confidence: 65%
“…Further testing of vasoactivity to garlic extracts showed that only RG, but not BG or AG, elicited a potent, dose-dependent dilation on the isolated coronaries. These findings show that positive effect of RG is probably mediated via its active metabolite allicin action on coronary endothelial function and vasoreactivity [121].…”
Section: Garlic and Endothelial Function Of Arteriesmentioning
confidence: 65%
“…In rats, compounds with antioxidant activities have been found to inhibit pulmonary hypertension and/or right ventricular dysfunction. Such compounds include probucol (19), N-acetylcysteine (16,23), tempol (9,20), erdosteine (46), allicin (43), pyrrolidine dithiocarbamate (17,39), superoxide dismutase (22), allopurinol (20), sulfur dioxide (21), resveratrol (7,52), and EUK-134 (35). In neonatal lambs with persistent pulmonary hypertension, superoxide dismutase was found to improve oxygenation, reduce oxidation (24), restore endothelial nitric oxide synthase expression and function (10), and normalize phosphodiesterase 5 (11).…”
Section: Evidence For Beneficial Effects Of Antioxidants In Animal Momentioning
confidence: 99%
“…87 Allicin, an organosulfur derivative, the major chemical constituent of A. sativum, protects against coronary endothelial dysfunction and right heart hypertrophy in pulmonary hypertension. 88 Rats were fed with 1% raw garlic-supplemented diet 1 day or 3 weeks before and 1 day after monocrotaline (MCT) injection to induce pulmonary hypertension, and changes in coronary endothelial cell function were measured. Coronary endothelial cell function, assessed with acetylcholine-induced dilation and N-nitro-L-arginine methyl ester-induced constriction, revealed marked attenuation in right coronary arteries of the MCT-treated rats.…”
Section: Concord Grapesmentioning
confidence: 99%
“…These outcomes further support the assumption that protection of coronary endothelial function may represent a new and novel therapeutic target for the management of heart hypertrophy and failure. 88 Garlic has also been shown to improve endothelial function in CAD in diabetic rats. 89 Fallon et al 90 reported that long-term oral feeding of freeze-dried garlic powder in rats was effective in preventing the growth of hypoxic pulmonary hypertension when the animals were subjected to 90 minutes of hypoxia.…”
Section: Concord Grapesmentioning
confidence: 99%